2021
DOI: 10.3390/ijms22094771
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide as a Target for Phytochemicals in Anti-Neuroinflammatory Prevention Therapy

Abstract: Nitric oxide (NO) is a neurotransmitter that mediates the activation and inhibition of inflammatory cascades. Even though physiological NO is required for defense against various pathogens, excessive NO can trigger inflammatory signaling and cell death through reactive nitrogen species-induced oxidative stress. Excessive NO production by activated microglial cells is specifically associated with neuroinflammatory and neurodegenerative conditions, such as Alzheimer’s and Parkinson’s disease, amyotrophic lateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 123 publications
0
26
0
Order By: Relevance
“…Furthermore, NO, a neurotransmitter that is produced through an amino acid, namely L-arginine, has been recognized to perform a distinctive physiological function [ 120 ]. Several investigations have revealed that NO exhibits a key function as a neurotoxic mediator related to mitochondrial impairment in a wide range of incapacitating neurodegenerative conditions, including PD [ 119 ].…”
Section: Pathogenesis Of Pdmentioning
confidence: 99%
“…Furthermore, NO, a neurotransmitter that is produced through an amino acid, namely L-arginine, has been recognized to perform a distinctive physiological function [ 120 ]. Several investigations have revealed that NO exhibits a key function as a neurotoxic mediator related to mitochondrial impairment in a wide range of incapacitating neurodegenerative conditions, including PD [ 119 ].…”
Section: Pathogenesis Of Pdmentioning
confidence: 99%
“…3-nitrotyrosine and protein carbonyls, these last produced mainly by the action of free radicals on the peptide chain or by oxidation of amino acids, are used as biomarkers of oxidative damage in the brain of AD and MCI [ 18 , 24 , 31 , 32 , 33 ]. NO, also classified as an RNS, is synthesized from L-arginine by three different isoforms of the enzyme NO synthase (NOS), i.e., endothelial (eNOS), neuronal (nNOS), and inducible (iNOS) which catalyze a two-step oxidation of L-arginine to NO and L-citrulline [ 34 , 35 ]. NO is a gaseous molecule, with a lone pair of electrons which can easily diffuse across membranes acting as a vasodilator, neuromodulator, and inflammatory mediator [ 34 ].…”
Section: Products Of Oxidative Damage In Admentioning
confidence: 99%
“…NO, also classified as an RNS, is synthesized from L-arginine by three different isoforms of the enzyme NO synthase (NOS), i.e., endothelial (eNOS), neuronal (nNOS), and inducible (iNOS) which catalyze a two-step oxidation of L-arginine to NO and L-citrulline [ 34 , 35 ]. NO is a gaseous molecule, with a lone pair of electrons which can easily diffuse across membranes acting as a vasodilator, neuromodulator, and inflammatory mediator [ 34 ]. At high concentration, NO reacts with superoxide radical and generates peroxynitrite, contributing to OS.…”
Section: Products Of Oxidative Damage In Admentioning
confidence: 99%
“…In this view, physiological compounds, including hormones, able to interfere with NO synthesis, by acting on the specific NOS isoforms expression, or NO-donor drugs can represent useful tools to prevent or treat motor dysfunctions. The importance of this topic is underlined by the emerging researches searching for natural or chemical compounds targeting NO [ 106 , 107 ]. However, it should be remembered that most of the data relating to the effects of NO on GI motor responses derive from studies carried out in animals and caution is mandatory when transferring them to humans.…”
Section: No and Possible Therapeutic Strategiesmentioning
confidence: 99%